Technical Analysis Of Road Functional Feasibility Traffic Management And Engineering In The Roads Bts. Palimanan City - Bts. Cirebon City - Santoso, Rochmad Bagus; Suraji, Aji; Aditya, Candra (Widyagama University of Malang, 2021)
city of Cirebon with Cirebon Regency (Palimanan) which plays an important role in the business of goods and services distribution services. This Road Function Worthiness Test aims to determine the feasibility of the road function on Bts roads. Palimanan City - Bts. Cirebon City, to find out the causes of malfunctioning based on traffic management and engineering on the road sections under study, and to propose follow-up actions if these roads do not meet the functional category. Test analysis function of road based on traffic management and engineering is performed by measuring deviation conditions in the field against a standard and the needs of the technical .But , in the preparation of this writer researching a thesis only 3 ( three ) of 7 seven the technical aspects of pertaining to management and traffic engineering. The technical aspects of third include: ( 1 ) technical the implementation of traffic management and engineering , ( 2 ) the way of technical equipment that are directly connected to road users , and ( 3 ) technical equipment a way that is not directly related to road users. The methodology that was used is by comparing technical standart on the condition in field with its reference to appendix ii minister for public works number 11 / prt / m / 2010 on procedures and requirements worthy function of road. The function of road shows that the worthy of its roads .City palimanan- towers. Cirebon city category in function to conditional ( ls ) means roads worthy to be operated but must be equipped with recommended have technical improvements. The cause of the non-functioning of the roads on the Bts road. Palimanan City - Bts. Cirebon City which is related to the technical implementation of traffic management and engineering, namely the components of markers, signs, sidewalks and crossings due to the absence of such equipment on roads. Cause not function roads related to technical equipment for the directly related to road users at components, markings , sign , sidewalks and apill because he does not meet the technical standard. The technical aspects of equipment in a way that is not directly related to road users because the conditions on the ground and the track the tent pin rumija safety not in accordance with technical standart